Analisis Sosiologi Sastra Cerpen “Yang Enak Dipandang” Karya Ahmad Tohari - Deti Asmalasari (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2023)
This research analyzes one of Ahmad Tohari's short stories entitled Eyes that are Good to Look at using a sociological literary analysis approach. This approach is used to determine the extent to which literary works are able to display social realities and problems that occur in society. Through the figure of Mirta Ahmad Tohari depicts the hard life of a blind beggar facing the ins and outs of life. The description of Mirta's suffering is a reality of life that is often encountered by lower class people.